2012
DOI: 10.1002/ajh.23105
|View full text |Cite
|
Sign up to set email alerts
|

Chronic transfusion practices for prevention of primary stroke in children with sickle cell anemia and abnormal TCD velocities

Abstract: ; for the TCD With Transfusions Changing to Hydroxyurea (TWiTCH) Trial Investigators Chronic transfusions are recommended for children with sickle cell anemia (SCA) and abnormal transcranial Doppler (TCD) velocities ( 200 cm/sec) to help prevent the occurrence of a primary stroke [1]. The goal is usually to maintain the sickle hemoglobin concentration (HbS) <30%; however, this goal is often difficult to achieve in clinical practice. The NHLBI-sponsored trial ''TCD With Transfusions Changing to Hydroxyurea (TWi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 11 publications
0
19
0
2
Order By: Relevance
“…This strategy is known to reduce stroke episodes. 17 The absence of any SCD-related mortality must be interpreted with caution. A retrospective cross-sectional hospital-based study may miss children with severe disease who have died in early childhood, and there may be individuals who have a mild disease phenotype and are never diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is known to reduce stroke episodes. 17 The absence of any SCD-related mortality must be interpreted with caution. A retrospective cross-sectional hospital-based study may miss children with severe disease who have died in early childhood, and there may be individuals who have a mild disease phenotype and are never diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large number of subjects in both cohorts were not able to achieve their prescribed target. Published literature has shown that the ability to achieve the requisite pre‐RBCX HbS/SC target can be quite variable (Aygun et al , ; Ware & Helms, ). The evidence for the chosen pre‐RBCX HbS/SC target of <30% was largely derived from the STOP (Stroke Prevention in Sickle Cell Anaemia) and STOP2 trials (Adams et al , ; Adams & Brambilla, ), the SWiTCH (Stroke With Transfusions Changing to Hydroxyurea) trial (Ware & Helms, ) and retrospective data (Pegelow et al , ).…”
Section: Patient Demographics Baseline Characteristics and Adverse Ementioning
confidence: 99%
“…The study inclusion criteria included: patients with SCA, age range 5.0-18.9 years at enrollment; previous completed overt clinical (index) stroke after age 1 year with central confirmation; $18 months of erythrocyte transfusions since the index stroke; transfusional iron overload with liver iron concentration $5.0 mg of iron/gram of dry weight liver or serum ferritin $500 ng/mL on 2 independent measurements; and adequate monthly erythrocyte transfusions with average HbS #45% for the past 6 months before enrollment. 25 Recognizing that the use of aspirin for secondary stroke prophylaxis varied among academic centers, the SWiTCH protocol neither recommended nor prohibited its use. A total of 161 subjects enrolled in the SWiTCH trial; 150 and 146 with entry brain MRI/MRA and TCD examinations during the initial screening period, respectively.…”
Section: Study Design and Subject Enrollmentmentioning
confidence: 99%